Compelling visuality : the work of art in and out of history - Farago, Claire J.; Zwijnenberg, Robert, 1954- (University of Minnesota Press, 2003)
Takes up the commonly unexplored question of what is actually present in art--what aspects have survived the vicissitudes of time. International and interdisciplinary, this volume conducts readers into a discussion of the significance of personal response to works of art.